Flüchtlinge in Deutschland: Herausforderung und Chancen - Holger Hinte; Ulf Rinne; Klaus F. Zimmermann (Wirtschaftsdienst, 2015)
Vom Flüchtlingszustrom erhoffen sich viele vor allem eine Linderung des Fachkräftemangels und eine Entlastung der sozialen Systeme. Die Integration der Flüchtlinge sollte also nicht als "Belastung", sondern als Zukunftsinvestition verstanden werden. Langfristig gibt es gute Aussichten, dass positive Wohlfahrtseffekte erzielt werden können. Kurzfristig müssen dazu die Potenziale von Flüchtlingen besser identifiziert und gestärkt werden. Ein Zuwanderungsgesetz ist aber weiterhin nötig. – – The massive influx of refugees, the largest since World War II, will have consequences on Germany's society, welfare institutions and labour market. Great challenges exist - mainly in terms of successful integration. But these young and motivated people may help alleviate the predicted demographic disruptions in the long run, especially if integration efforts are effective. In the short run, their skills and qualifi cations should thus be systematically assessed in order to provide them with adequate language courses and vocational training. Despite this massive influx of migrants, Germany still needs to reform its immigration policy to attract skilled migrants.
Keywords: F22; J61; K37; 330